Leg Amputation for an Extensive, Severe and Intractable Sickle Cell Anemia Ulcer in a Brazilian Patient. (April 2014) - Queiroz, Ana Maria Mach; Campos, Jessica; Lobo, Clarisse; Bonini-Domingos, Claudia Regina; Cardoso, Gilberto; Ballas, Samir K.
Abstract A 35-year-old African Brazilian patient had sickle cell anemia complicated with recurrent vasoocclusive (VOC) crises and refractory painful leg ulcers for 16 years. The ulcers started over both medial malleoli and expanded gradually. The ulcer on the left leg spread from the foot to the knee circumferentially and was refractory to all forms of therapy within the frame work of multi-disciplinary care. The patient agreed to a below the knee amputation of the left leg. He felt much better after the amputation but developed severe neuropathic phantom pain that was well controlled medically. He could differentiate the sickle cell anemia and ulcer pain from the neuropathic pain. About 6 months after the amputation he had dengue fever with fatal outcome. This is the first report of treatment of refractory sickle cell anemia leg ulcer with amputation and probably the first report of a Brazilian patient with sickle cell anemia and dengue fever.